Aborta neatļauta izdarīšana - Piternika, Laila (Latvijas Universitāte, 2010)
Bakalaura darba tema ir „Aborta neatlauta izdarišana. Aborti visur pasaule tiek veikti jau vairaku gadsmistu garuma, bet tikai 19.gs. saka ieviest izveles grutniecibas partraukšanu. Tacu tieši musdienas to veikšana ir ipaši aktualizejusies. Tas ir visiem zinams fakts, ka katru dienu pasaule mirst tukstošiem nedzimušu bernu, matem izveloties veikt abortu. Aborts uzskatams par stridigu jautajumu no vairakam pusem- gan no etiskas, gan moralas un juridiskas un lidz ar to, sastopami gan aborta pretinieki, gan ari kaisligi ta atbalstitaji. Tieši tapec auotore izvelejas šo tematu- lai noskaidrotu kas ir tie problemjautajumi kapec valda tik divejads uzskats par grutniecibas partraukšanu un izpetot LR likumdošanu, kas regule grutniecibas partraukšanu, noskaidrotu vai tur atrodamas kadas nepilnibas. Ari Latvija tiek regulets šis jautajums un kriminallikuma ir ieklauts pants par aborta nelikumigu izdarišanu.

The theme of bachelor work is „Unauthorized performin of an abortion”. Abortion has been performed everywhere in the world during centuries and it still is a well known fact that each day in the world many unborn children are killed through abortion. The sixth commandment which stipulates: "You shall not kill," obliges not only christians as a moral law, but also every human person including non-believers since it is also a natural law. Constitutions of many countries stipulate that every human person has a right to life. Not only that human life is sacred, but it is also inviolable. No one therefore, has the right to take away human life; instead we have the duty to care for it, to protect it and to defend it. This situation is due to the fact that abortion is legalised in most countries for unjustifiable reasons for example for the deformity of the unborn child, for economic difficulty, for psychological health of the mother, etc. Some countries defend the so-called right of the woman to decide whether to abort or not. This so called right of the woman to freedom of choice, derives from right to private life of each person, protected by the Constitution.
Unauthorized performing of an abortion
Keywords: Juridiskā zinātne